DEVELOPMENT OF MULTIPLEX PCR ASSAY FOR MEAT PRODUCTS AUTHENTICATION: TARGETING DOUBLE GENE - Hossain, M A Motalib; Uddin, Syed Muhammad Kamal; Bonny, Sharmin Quazi; Johan, Mohd Rafie; Ali, Md. Eaqub (MATTER: International Journal of Science and Technology, 2019)
Authentication of the species origins of animal-originated food products is a rapidly growing field because of its direct relevance to public health as well as people’s religious and cultural traditions. Current polymerase chain reaction assay (PCR) based methods to authenticate the animal materials in food chain are based on mainly single gene targets which are generally longer in length and thus breakdown during food processing treatments. Consequently, there is a chance of a false negative result. For the first time, here we targeted double gene sites in short-amplicon length multiplex PCR (mPCR) for confirmed detection and differentiation of bovine, buffalo and porcine materials in food chain. Multiple targets detection in single assay saves analytical cost and time. The design of primer sets for mPCR assay is more complex and complicated because all biomarkers are annealed to their respective targets under a single set of PCR conditions. Inaccurately designed primers might prompt less amplification or formation of primer-dimer and/or non-specific products. Here we approached the techniques to design biomarkers for the development of double gene targeted mPCR assay. Mitochondrial cytochrome b (cytb) and NADH dehydrogenase subunit 5 (ND5) genes were targeted to design six different biomarkers, two for each of cow (121 and 106 bp), buffalo (90 and 138 bp) and pig (73 and 146 bp). The in-silico specificity of the developed primers was checked against three targets and 28 non-target species. Complete sequence matching was found only with target species, and 3−18 nucleotides (12.5−80%) mismatches were found with other species. The pairwise distance was also computed using the neighbour-joining method; the lowest and highest distances were observed between 0.144 and 1.993. These indicated adequate genetic distances among the studied species, eliminating the probability of any cross-target detection and thus facilitated the target detection through mPCR assay.